IMPLEMENTATION OF ELECTRE ALGORITHM IN DECISION SUPPORT SYSTEM FOR SELECTING EXEMPLARY STUDENT - Eka Pandu Cynthia; Edi Ismanto (LPPM Nusa Mandiri, 2020)
One of the activities undertaken by the school to reward students for increasing motivation and enthusiasm for learning is the process of selecting exemplary students. Based on the observation of one of the junior high schools in Pekanbaru, the problem of difficulty in selecting the model students was obtained. This is because there are so many aspects and components of assessment that must be considered and taken into account by the school, both in terms of academic and non-academic students. Decision support system (SPK) plays an important role in supporting a decision, this research makes a model design in the form of a decision support system by applying the ELECTRE (Elimination Et Choix Traduisant La Relite) algorithm. The ELECTRE method is one of the Multi-Attribute Decision Making (MADM) methods that can provide decision recommendations based on the complexity of the attributes or criteria used in a decision support system. In this study, there are 8 components of the criteria used in the process of selecting exemplary students, namely the average report card, ranking, absenteeism, morals, achievements, organization, attitudes, and points of the violation. Based on the test results of the model built, it was found that the ELECTRE algorithm was able to select and rank 6 alternative model students based on assessment components and predetermined criteria. With the results of student A obtaining the highest aggregate value (2), followed by students B, C, D, E, and F with aggregate value 1 and finally student G with aggregate value 0. So student A can be proposed as a model student